2015
DOI: 10.1016/j.jbiomech.2014.11.038
|View full text |Cite
|
Sign up to set email alerts
|

Chronic changes in the articular cartilage and meniscus following traumatic impact to the lapine knee

Abstract: The objective of this study was to induce anterior cruciate ligament (ACL) and meniscal damage, via a single tibiofemoral compressive impact, in order to document articular cartilage and meniscal changes post impact. Tibiofemoral joints of Flemish Giant rabbits were subjected to a single blunt impact that ruptured the ACL and produced acute meniscal damage. Animals were allowed unrestricted cage activity for 12 weeks before euthanasia. India ink analysis of the articular cartilage revealed higher degrees of su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 47 publications
3
37
0
Order By: Relevance
“…The observed decreases in the α (or stiffness) term from control to impacted menisci were not surprising, as the experimental data utilized for this study showed decreases in in meniscal instantaneous and equilibrium moduli (Fischenich et al, 2014a), while a similar study of an OA transection model also found decreased indentation stiffness (Fischenich et al, 2014b). Our results show that in addition to decreases in stiffness, the time dependent mechanical properties of the menisci were altered following tibiofemoral impact.…”
Section: Discussionsupporting
confidence: 50%
See 4 more Smart Citations
“…The observed decreases in the α (or stiffness) term from control to impacted menisci were not surprising, as the experimental data utilized for this study showed decreases in in meniscal instantaneous and equilibrium moduli (Fischenich et al, 2014a), while a similar study of an OA transection model also found decreased indentation stiffness (Fischenich et al, 2014b). Our results show that in addition to decreases in stiffness, the time dependent mechanical properties of the menisci were altered following tibiofemoral impact.…”
Section: Discussionsupporting
confidence: 50%
“…Changes to the GAG content could therefore disrupt tissue permeability. Previous work shows a decrease in GAG content in menisci at twelve weeks post injury (Fischenich et al, 2014a; Fischenich et al, 2014b). Increases in permeability could lead to an overloading of the solid matrix and fibers, resulting in further degradation of these solid constituents.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations